Dual experimental and computational approach to elucidate the effect of Ga on Cu/CeO2–ZrO2 catalyst for CO2 hydrogenation. (November 2022) - Attada, Yerrayya; Velisoju, Vijay K.; Mohamed, Hend Omar; Ramirez, Adrian; Castaño, Pedro
Abstract: Cu–Ga catalysts are potential candidates for activating the selective and stable hydrogenation of carbon dioxide to methanol and dimethyl ether. This work explores the structure–function relationship in specific Cu–Ga/CeO2 –ZrO2 catalysts with different Ga loadings. Combining experiments with density functional theory calculations, we find the most well-balanced Cu–Ga interphase (structure) and promote specific mechanistic pathways of the reaction (function). The experiments yielded the highest selectivity of the desired products when the Cu and Ga amounts were equal. The experimental work and density functional theory calculations demonstrated that methanol is formed through the carboxyl pathway on the Cu catalyst, while Ga promotes the formate pathway. Consequently, the productivities of both methanol and dimethyl ether are enhanced. The experimental results match well with the theoretical calculations. Comparing our results with other Ga-promoting systems, we also prove that Cu achieves better balance than Ni and Co. Graphical Abstract: ga1 Highlights: An experimental and modeling study on the effect of Ga on Cu catalyst for CO2 reduction. Experiments were performed on a set of Cu-Ga catalysts with different Ga contents. The catalysts were tested in CO2 hydrogenation, demonstrating the promoting effect of Ga. Ab initio calculations showed that Ga activates CO2 and stabilizes the intermediates. Our calculations correlate with the experimental observations in terms of catalyst performance.